Diversity Dynamics: How Local Religious Groups Appear, Persist, or Disappear over Time - Senn, Jeremy (Journal for the scientific study of religion, 2024)
Religious diversity is often described and measured statically. This article goes a step further by describing how congregational religious diversity changes over time, and by exposing the mechanisms underlying these changes. We combine data from two censuses (from 2008 and 2020) of congregations in Switzerland with a sample-based national congregation study conducted in 2008. Our main findings are the following: (1) overall, the number of congregations is in decline. (2) Religious diversity remains stable, but underlying features of religious diversity change radically. For example, established Christian congregations almost only disappear while Orthodox Christians see almost only new congregations. (3) Rural areas lose congregations mainly because established Christian groups merge their parishes, while urban areas have a high turnover. (4) Some congregational characteristics such as religious tradition, number of participants or presence of a meeting space significantly predict a congregation's likelihood of disappearing, in contrast to other variables, including income.